The Role of Universities in Community Service - Kazem, Asst. Lect. Dr. Alaa Abbas Kazem; Najib, Asst. Prof. Dr. Riyam Ghanem Najib (Sulaimani Journal for Humanities, 2026)
The research presented a theoretical and practical study of community service activities in the College of Basic Education / Al-Muthanna University, explaining the concept of community service and its most important fields, with the inclusion of the activities of the College of Basic Education between the years (2020-2024). To enhance its importance, a practical questionnaire was adopted and distributed to a sample of college members amounting to (22 individuals), who provided their answers and suggestions. The research concluded with a number of conclusions and suggestions.
Keywords: Community service; community; universities; College of Basic Education; University of Muthanna